PEMBENTUKAN UNDANG-UNDANG DALAM PERSPEKTIF PUTUSAN MAHKAMAH KONSTITUSI - ., Qomaruddin (Jurnal Legislasi Indonesia, 2009)
The Constitutional Court has an authority in judging at first and final levelof the decision that shall be final and binding also obtain permanent legalforce since the end of spoken/read, but there are some decisions that cannot be directly implemented due to need follow-up with the formation ofnew laws or law amendment, for example Constitutional Court decisionNumber 5/PUU-IV/2007 that grant the petition of the Petitioner regarding“individual candidates in the election of regional leader and regional leaderproxy”, can not be directly applied operationally, without following up withthe making of the Law Amendment of Law Number 32 Year 2004 regardingRegional Government. Legislation making in order to follow up the decisionof the Constitutional Court legally permissible, although the law in questionoutside the National Legislation Program (Prolegnas). In making legislation,the Constitutional Court decision can be used by legislators as a referenceto determine the constitutionality of draft of law, against the Constitution ofthe Republic of Indonesia Year 1945.